1947
DOI: 10.1029/tr028i001p00105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of removal of stream‐bank vegetation upon water yield

Abstract: Abstract--This is a preliminary report of results of a study wherein vegetation has been cut along the stream bank of a 22-acre watershed on the Coweeta Experimental Forest. Previous measurements on this forest have shown that complete removal of vegetation results in notable gains in water yield because of a reduction in transpiration. The cutting of riparian growth has also resulted in an increase in yield of sufficient magnitude to be significant in water-resource management.Preliminary examination of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

1969
1969
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 3 publications
(6 reference statements)
5
49
0
Order By: Relevance
“…This possible modification of the streamflow generation, derived from the virtual experiment is in agreement with the numerous field studies which demonstrated the increase of the water yield after clear cutting of riparian vegetation (Dunford and Fletcher, 1947;Ingebo, 1971;Dye and Poulter, 1995;Scott, 1999). However, such an extrapolation has to be done carefully because of the complex adaptation of riparian vegetation to new conditions.…”
Section: Synthesis: Overall Schematic Of the Hillslope Hydrodynamic Fsupporting
confidence: 70%
See 2 more Smart Citations
“…This possible modification of the streamflow generation, derived from the virtual experiment is in agreement with the numerous field studies which demonstrated the increase of the water yield after clear cutting of riparian vegetation (Dunford and Fletcher, 1947;Ingebo, 1971;Dye and Poulter, 1995;Scott, 1999). However, such an extrapolation has to be done carefully because of the complex adaptation of riparian vegetation to new conditions.…”
Section: Synthesis: Overall Schematic Of the Hillslope Hydrodynamic Fsupporting
confidence: 70%
“…Conversely, insufficient water outflow in the model can result from too low riparian uptake or seepage into the river. Dunford and Fletcher (1947) on the Coweeta Experimental Forest, showed that a riparian forest could actually extract more water than expected. Following Jarvis (1989), another possible cause of insufficient water outflow is a compensation effect where reduced transpiration in the water-stressed parts of the root zone is balanced by increased transpiration in other parts.…”
Section: Year-to-year Variability Of the Simulated Functioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Soils are Ultisols and are represented by Typic Hapludults with Cowee-Evard and Trimont gravelly loam series being the predominant soils on the watershed. The Coweeta Basin was selectively logged between 1909 and 1923, after which the only disturbances to WS 6 were the chestnut blight of the 1930s, and cutting of the riparian zone of 1-1 ha in 1942 (Dunford and Fletcher, 1947). By 1957, the cleared area had completely regrown and the basin as a whole was covered by an oak-hickory stand of low quality, typical of north-facing slopes in the Southern Appalachians, with scattered openings of rhododendron, mountain laurel, and other low shrubby species (Hibbert, 1969).…”
Section: Site Description and Historymentioning
confidence: 99%
“…In July 1942, 12% of the catchment (2.7 acres) along the stream was cut to determine the effect on water yield of cutting streamside vegetation [Dunford and Fletcher, 1947]. Diurnal fluctuations of streamflow were damped for several weeks by this treatment, but the savings in evapotranspiration were not sufficient to be detected as a seasonal or annual increase in streamflow.…”
mentioning
confidence: 99%